A histopathologic schema to quantify the burden of cardiac amyloidosis: Relationship with survival and echocardiographic parameters. Issue 2 (28th December 2018) - Mehta, Priya; Chapel, David B.; Goyal, Neha; Yu, Dong Bo; Mor‐Avi, Victor; Narang, Akhil; Addetia, Karima; Sarswat, Nitasha; Lang, Roberto M.; Husain, Aliya N.; Patel, Amit R.
Abstract : Background: Despite routine use of echocardiographic parameters to evaluate the severity of cardiac amyloidosis (CA), this methodology has not been well validated. We developed a histopathologic schema for quantifying CA burden and evaluated its relationship with clinical outcomes. Additionally, echocardiographic parameters were tested as potential noninvasive indices of CA burden. Methods: We retrospectively studied 59 patients with CA (17 light chain, 42 transthyretin) who underwent endomyocardial biopsies. Light microscopy with staining was used to categorize CA burden as mild‐to‐moderate (<50%) or high (≥50%). Kaplan‐Meier survival analysis was performed for the two groups. In 34 patients with good‐quality echocardiograms, we measured left ventricular volumes, ejection fraction (EF), interventricular septal thickness (IVSt), posterior wall thickness (PWt), LV mass, lateral e′‐velocity, and global longitudinal strain (GLS). These parameters were compared between the two groups. Results: Thirty‐five patients had mild‐to‐moderate and 24 severe amyloid burden. Kaplan‐Meier curves demonstrated a trend toward worse mortality with high CA burden, which was more common and associated with higher mortality specifically in transthyretin‐type patients. Echocardiography‐derived IVSt, PWt, and LV mass were directly related to CA burden, while LV EF, e′‐velocity, and GLS magnitude were inversely related to CA burden. Conclusions: Our findings provided a signal that CA burden is a clinically important entity with potentially valuable prognostic information. Echocardiographic parameters of LV anatomy and function correlate with histopathologic burden of CA, which is inversely related to survival. Further studies are needed to determine whether these parameters could be used as imaging biomarkers of treatment‐related changes in CA burden.